The above-ground coarse wood productivity of 104 Neotropical forest plots - Malhi, Yadvinder Singh; Baker, Timothy R.; Phillips, Oliver L.; Almeida, Samuel Miranda; Alvarez, Esteban; Arroyo, Luzmila P.; Chave, Jérôme; Czimczik, Claudia I.; Di Fiore, Anthony; Higuchi, Niro; Killeen, Timothy J.; Laurance, Susan G.W.; et al. (Global Change Biology, 2004)
The net primary production of tropical forests and its partitioning between long-lived carbon pools (wood) and shorter-lived pools (leaves, fine roots) are of considerable importance in the global carbon cycle. However, these terms have only been studied at a handful of field sites, and with no consistent calculation methodology. Here we calculate above-ground coarse wood carbon productivity for 104 forest plots in lowland New World humid tropical forests, using a consistent calculation methodology that incorporates corrections for spatial variations in tree-size distributions and wood density, and for census interval length. Mean wood density is found to be lower in more productive forests. We estimate that above-ground coarse wood productivity varies by more than a factor of three (between 1.5 and 5.5 Mg C ha-1a-1) across the Neotropical plots, with a mean value of 3.1 Mg C ha-a-1. There appear to be no obvious relationships between wood productivity and rainfall, dry season length or sunshine, but there is some hint of increased productivity at lower temperatures. There is, however, also strong evidence for a positive relationship between wood productivity and soil fertility. Fertile soils tend to become more common towards the Andes and at slightly higher than average elevations, so the apparent temperature/productivity relationship is probably not a direct one. Coarse wood productivity accounts for only a fraction of overall tropical forest net primary productivity, but the available data indicate that it is approximately proportional to total above-ground productivity. We speculate that the large variation in wood productivity is unlikely to directly imply an equivalent variation in gross primary production. Instead a shifting balance in carbon allocation between respiration, wood carbon and fine root production seems the more likely explanation. © 2004 Blackwell Publishing Ltd.
Keywords: Aboveground Production; Carbon Cycle; Forest; Neotropical Region; Soil Fertility; Amazonia; South America; Antidesma Platyphyllum